Rural community perceptions of antibiotic access and understanding of antimicrobial resistance: qualitative evidence from the Health and Demographic Surveillance System site in Matlab, Bangladesh - Chowdhury, Moyukh (Glob Health Action, 2020)
BACKGROUND: The use of large quantities of antimicrobial drugs for human health and agriculture is advancing the predominance of drug resistant pathogens in the environment. Antimicrobial resistance is now a major public health threat posing significant challenges for achieving the Sustainable Development Goals. In Bangladesh, where over one third of the population is below the poverty line, the achievement of safe and effective antibiotic medication use for human health is challenging. OBJECTIVE: To explore factors and practices around access and use of antibiotics and understanding of antimicrobial resistance in rural communities in Bangladesh from a socio-cultural perspective. METHODS: This qualitative study comprises the second phase of the multi-country ABACUS (Antibiotic Access and Use) project in Matlab, Bangladesh. Information was collected through six focus group discussions and 16 in-depth interviews. Informants were selected from ten villages in four geographic locations using the Health and Demographic Surveillance System database. The Access to Healthcare Framework guided the interpretation and framing of the findings in terms of individuals’ abilities to: perceive, seek, reach, pay and engage with healthcare. RESULTS: Village pharmacies were the preferred and trusted source of antibiotics for self-treatment. Cultural and religious beliefs informed the use of herbal and other complementary medicines. Advice on antibiotic use was also sourced from trusted friends and family members. Access to government-run facilities required travel on poorly maintained roads. Reports of structural corruption, stock-outs and patient safety risks eroded trust in the public sector. Some expressed a willingness to learn about antibiotic resistance. CONCLUSION: Antimicrobial resistance is both a health and development issue. Social and economic contexts shape medicine seeking, use and behaviours. Multi-sectoral action is needed to confront the underlying social, economic, cultural and political drivers that impact on the access and use of antibiotic medicines in Bangladesh.